Hygienic assessment of new architectural and planning solutions of buildings of psychiatric health care facilities - Polka, N.S.; Makhniuk, V.M.; Chorna, V.V.; Podolian , V.M.; Yurchenko , S.T. (Medicni Perspektivi, 2022)
Aim: to conduct a hygienic assessment of new architectural and planning solutions of psychiatric health care facility buildings in Ukraine and give a comparative description of the sanitary standards of the latter in the EU. The study was conducted based on the analysis of State Building Norms (SBN) B.2.2-10:2019 “Buildings and structures. Health care facilities” (draft, final revision), scientific sources of domestic and foreign scientists. A survey of the chief physicians of psychiatric hospitals of Ukraine concerning safe sanitary and hygienic, anti-epidemic conditions for the functioning of psychiatric health care facilities was conducted. We consider it necessary to present more carefully architectural and planning solutions in the relevant section of SBN B.2.2-10:2019 (draft, final revision) or to use the opportunity specified in the introduction to these Norms, and to supplement them with the Manual on the design of psychiatric health care facilities, taking into account the experience of the European Union. To create an appropriate “therapeutic environment” in new domestic mental health care facilities, it is necessary to implement European requirements in the design of these facilities with the involvement of multidisciplinary groups: (from architects to nurses, from construction contractors to patients) and supplement SBN B.2.2-10:2019 “Buildings and structures. Health care Facilities” of Ukraine with a guide for designing facilities of a new type of “Mental Health Centers” as in the Republic of Poland. We have developed and sent to the chief physicians of psychiatric hospitals of Ukraine «Questionnaire for scientific sanitary and epidemiological assessment of the conditions of placement of a psychiatric health care facility”. Based on the analysis of the block of questions on sanitary and antiepidemic and sanitary and hygienic parameters that characterize the buildings of domestic psychiatric hospitals, the location of medical structures and auxiliary units on the land plot, i.e. the design of buildings is determined. In particular, 50% of psychiatric hospitals are housed in combined buildings, 25% have a pavilion system (separate buildings), 12.5% each have a centralized system (all in one building) and a block system. The number of stories of psychiatric hospitals up to 2 is 50%, up to 3 – 37.5% and up to 5 stories in those which have been under construction since 1960 – 12.5%. Analysis of the questionnaire block on the conditions of stay, treatment, rehabilitation of the mentally ill revealed the possibility of organizing occupational therapy in 12.5% of psychiatric hospitals, where special workshops are equipped and patients can acquire professional skills. Physiotherapy rooms are equipped in 50% of psychiatric hospitals. Low provision of patients with furniture was revealed: 25% of patients partially have proper desk, 75% do not have it; 50% are provided with proper chairs; 62.8% use proper bedside tables and 25% – closets for storing personal clothes.